2007
DOI: 10.1037/0735-7044.121.5.877
|View full text |Cite
|
Sign up to set email alerts
|

Food reinforcement, the dopamine D₂ receptor genotype, and energy intake in obese and nonobese humans.

Abstract: The authors measured food reinforcement, polymorphisms of the dopamine D2 receptor (DRD2) and dopamine transporter (DAT1) genes, and laboratory energy intake in 29 obese and 45 nonobese humans 18-40 years old. Food reinforcement was greater in obese than in nonobese individuals, especially in obese individuals with the TaqI A1 allele. Energy intake was greater for individuals high in food reinforcement and greatest in those high in food reinforcement with the TaqI A1 allele. No effect of the DAT1 genotype was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
256
5
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 279 publications
(278 citation statements)
references
References 57 publications
15
256
5
2
Order By: Relevance
“…In addition we also document a significant association between D2 receptors and metabolism in somatosensory cortex that could modulate the reinforcing properties of food (Epstein et al, 2007) and that merits further investigation. Brain maps obtained with SPM showing the areas where the correlations between striatal D2 receptor availability and brain glucose metabolism were significant.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition we also document a significant association between D2 receptors and metabolism in somatosensory cortex that could modulate the reinforcing properties of food (Epstein et al, 2007) and that merits further investigation. Brain maps obtained with SPM showing the areas where the correlations between striatal D2 receptor availability and brain glucose metabolism were significant.…”
Section: Resultsmentioning
confidence: 57%
“…There is also evidence that DA modulates the somatosensory cortex in the human brain (Kuo et al, 2007). Inasmuch as DA stimulation signals saliency and facilitates conditioning (Zink et al, 2003, Kelley, 2004), DA's modulation of the somatosensory cortex's response to food is likely to play a role in the formation of conditioned association between food and food-related environmental cues and in the enhanced reinforcing value of food that occurs in obesity (Epstein et al, 2007).…”
Section: Correlation Between D2r and Somatosensory Cortexmentioning
confidence: 99%
“…Some evidence suggests that there may be differences in the neural mechanisms for the motivation to eat and to be physically active. Studies of children (Temple, Legierski, Giacomelli, Salvy & Epstein, unpublished results) and adults [19,20] have found that the RRV of food was more strongly associated with energy intake in ad libitum eating tasks than liking for food. In contrast, the present study found that both RRV and liking of physical activity were independently associated with physical activity participation and that MVPA was greatest only when the individual had relatively high RRV and liking of physical activity.…”
Section: Discussionmentioning
confidence: 95%
“…Salamone and Correa [13], however; discuss the evidence that dopamine antagonists and nucleus accumbens dopamine depletions do not affect behavior directed towards the acquisition and consumption of food per se, but does alter effort-related choice, shifting choice to lower-cost less preferred foods. Research suggests that wanting is a stronger predictor of energy intake than liking in animals [18] and reinforcing value is a stronger predictor of energy intake than liking in humans [19,20]. Reinforcing value has been related to usual physical activity [9], but to our knowledge there is no research that has tested whether the relative reinforcing value (RRV) and liking aspects of physical activity are independently associated with participation in MVPA or the relative importance of each component for children's usual participation in more vigorous types of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Generation and analysis of dopamine D2R knockout (D2R À/À ) mice indeed demonstrated that the D2R plays a key role in dopaminergic neurotransmission [9][10][11][12][13]. In human, genetic studies with obese individuals showed possible association of the polymorphisms of the D2R gene with obesity [14][15][16][17]. Although the precise mechanism has not been established, these observations indicate that normal D2R function might be important in the maintenance of normal eating behavior and also in the regulation of energy balance.…”
Section: Introductionmentioning
confidence: 99%